Analisis Produktivitas Kerja Karyawan Bidang Operasional pada Colorbox Sun Plaza Medan - Disti Aulia Putri; Dini Anggraini; Gina Sonia Simbolon; Irwan Nopian Sinaga (Master Manajemen, 2025)
This study aims to determine the work productivity of employees at the Colorbox Sun Plaza Medan store, a local fashion retailer serving the young women’s segment. The research employs a descriptive qualitative method with a case study approach. Data were obtained through in-depth interviews with five informants, comprising one Store Manager, one Supervisor, and three employees. The results show that employee productivity is measured by sales target achievement, display area compliance, minimal inventory losses, and positive customer feedback. Factors affecting productivity include work motivation, operational management systems, task allocation, and a supportive work environment. Although overall productivity is satisfactory, challenges such as low visitor traffic and weak supervision in the fitting room area were identified. Therefore, enhancements in motivation, training, and the strengthening of supervisory systems are needed to ensure sustained improvements in work productivity.